2019
DOI: 10.1186/s12934-019-1073-5
|View full text |Cite
|
Sign up to set email alerts
|

Growth-dependent recombinant product formation kinetics can be reproduced through engineering of glucose transport and is prone to phenotypic heterogeneity

Abstract: BackgroundEscherichia coli W3110 and a group of six isogenic derivatives, each displaying distinct specific rates of glucose consumption were characterized to determine levels of GFP production and population heterogeneity. These strains have single or combinatory deletions in genes encoding phosphoenolpyruvate:sugar phosphotransferase system (PTS) permeases as PtsG and ManX, as well as common components EI, Hpr protein and EIIA, also the non-PTS Mgl galactose/glucose ABC transporter. They have been transforme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 52 publications
1
30
0
Order By: Relevance
“…reported with high capability of withstanding different toxic chemicals [21][22]. Consequently, W3110 is a suitable strain to be equipped with the T7RNAP onto the chromosome.…”
Section: Conversion Of Lysine To Cadaverine By the Engineered W3110 Smentioning
confidence: 99%
See 1 more Smart Citation
“…reported with high capability of withstanding different toxic chemicals [21][22]. Consequently, W3110 is a suitable strain to be equipped with the T7RNAP onto the chromosome.…”
Section: Conversion Of Lysine To Cadaverine By the Engineered W3110 Smentioning
confidence: 99%
“…Alternatively, the K-12 strains such as MG1655 and W3110, are commonly used as they express more heat shock genes, are less sensitive to certain stress and also possess higher rates of glucose consumption [21][22]. A comparative proteomics study between BL21 and W3110 manifested that W3110 maintained growth and metabolism at lower oxygen levels, thus enabling foreign protein to be gradually expressed [23].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased enzyme availability might lead to high sugar accumulation in the fermentation broth, especially when exponential feeding is applied (Slouka et al, 2018a), as already stressed cells might additionally suffer from osmotic stress, triggering cell death (Slouka et al, 2019). It is shown that high sugar uptake rates tend to shift toward acetate formation, finally leading to decreased levels of production (Fragoso-Jiménez et al, 2019). Therefore, appropriate feeding rates beneath μ max should be set to avoid overflow metabolism; however, acetate production can also be significantly reduced using engineered strains, as shown by Lara et al (2008), Valgepea et al (2010), Peebo et al (2015), and Anane et al (2017).…”
Section: The Current State Of E Coli Fed-batch Process Understandingmentioning
confidence: 99%
“…A reduction of cell densities, temperature, or separation of biomass growth and RPP might facilitate stability in continuous processes (Rugbjerg and Sommer, 2019). Enabling higher sugar uptake with engineered strains shows that specific productivity and specific sugar uptake rates were correlated in a bell-shaped curve; extreme sugar uptake rates lead to fermentative growth (Basan et al, 2015; Peebo et al, 2015; Basan, 2018; Fragoso-Jiménez et al, 2019). The metabolic load therefore has to be considered, and feeding strategies and model-based approaches that consider the shifts in the growth rate have to be established (Kopp et al, 2018).…”
Section: The Current State Of E Coli Fed-batch Process Understandingmentioning
confidence: 99%
See 1 more Smart Citation